2013
DOI: 10.1136/bcr-2013-201022
|View full text |Cite
|
Sign up to set email alerts
|

Acute liver injury secondary to sertraline

Abstract: Sertraline is widely prescribed to treat depression and anxiety disorders. However, hepatitis secondary to its use is a rare entity. We report the case of a 26-year-old woman in her 20th week of pregnancy presented with nausea, vomiting, malaise and dark urine. This occurred 6 months after sertraline 50 mg daily was started for the treatment of depression. Three weeks prior to her presentation, the dose of sertraline was increased to 100 mg daily. The patient's liver biochemical profile demonstrated increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…Antidepressant-induced liver injury is generally considered to be dose independent. However, cases of hepatic toxicity following antidepressant dosage escalation have been reported for duloxetine, nefazodone, mianserin, and sertraline (30,38,43,44) (Table 2); in one case report, reduction of the daily dose was followed by reversal of mianserin-associated liver injury (43) ( Table 2). In clinical trials of agomelatine, aminotransferase values .33ULN were observed in 1.4% of patients treated with 25 mg/day and 2.5% of those treated with 50 mg/day, compared with 0.6% of the placebo group (147,151).…”
Section: Risk Factorsmentioning
confidence: 99%
“…Antidepressant-induced liver injury is generally considered to be dose independent. However, cases of hepatic toxicity following antidepressant dosage escalation have been reported for duloxetine, nefazodone, mianserin, and sertraline (30,38,43,44) (Table 2); in one case report, reduction of the daily dose was followed by reversal of mianserin-associated liver injury (43) ( Table 2). In clinical trials of agomelatine, aminotransferase values .33ULN were observed in 1.4% of patients treated with 25 mg/day and 2.5% of those treated with 50 mg/day, compared with 0.6% of the placebo group (147,151).…”
Section: Risk Factorsmentioning
confidence: 99%
“…Autoimmune (autoantibodies) and immune allergic features (rash, fever, and eosinophilia) are uncommon. Acute liver failure due to sertraline has been described but very rarely [4] [6].…”
Section: Discussionmentioning
confidence: 99%
“…Christopher F describe that in rare instances of acute clinically apparent episodes of liver injury with marked liver enzyme elevations with or without jaundice been reported in patients on sertraline [4]. Croft H found that sertraline cause sexual dysfunction [3].…”
Section: Literature Reveiwmentioning
confidence: 99%
See 2 more Smart Citations